Assessing the effectiveness of the water purification process in removing clostridium perfringens spores as a surrogate for protozoan parasites - Schubart, Annah Lindiwe (Vaal University of Technology, 2022)
The World Health Organization (WHO) provides guidelines for assessing the microbiological risk associated with drinking water using a Quantitative Microbial Risk Assessment (QMRA). Microbiological risk in water may arise from pathogens such as protozoan parasites Giardia and Cryptosporidium. The risk presented by Giardia and Cryptosporidium in water is increased by the fact that these pathogens are resistant to disinfection by chlorine. It is costly to monitor treated water for the presence of Cryptosporidium and Giardia, therefore a surrogate was used to carry out the evaluations. This research first determined the efficacy of the conventional water treatment processes in removing Clostridium perfringens spores as a surrogate for protozoan parasites (Cryptosporidium oocysts and Giardia cysts). We estimated the number of protozoan parasites that can pass through the drinking water treatment barriers. This removal efficiency can then estimate the number of protozoan parasites that can survive drinking water purification. The study conducted a simulated jar test under predetermined conditions using three different coagulation combinations: (i) Polyelectrolyte, (ii) polyelectrolyte and slaked lime, and (iii) slaked lime and activated sodium silicate. The three regimens (polyelectrolyte, polyelectrolyte and slaked lime, and slaked lime and activated sodium silicate) were tested each at low temperatures (12.8 ± 0.4°C), normal temperatures (17.2 ± 0.9°C), and at high temperatures (20.3 ± 0.1°C). The three coagulant combinations (polyelectrolyte, polyelectrolyte and slaked lime, and slaked lime and activated sodium silicate) were also tested under normal temperature conditions at high water turbidity. Percentage and log reduction for C. perfringens spores were calculated for each water treatment unit. A percentage reduction for turbidity was calculated for each water treatment unit. Pre-experiments were conducted to determine the suitability of the filter membranes and media to be used for analysing the water samples for the study. The 0.45 μm filter membrane and the Perfringens Agar Base (PAB) were selected and used. Experiments conducted at low temperatures (12.8 ± 0.4°C) showed C. perfringens spore log reductions of infinity or 100% when the polyelectrolyte and a combination of polyelectrolyte and slaked lime were used. Under normal conditions (17.2 ± 0.9°C), C. perfringens spores log reductions of up to 2.0 or 98.9 ± 0.4% were observed using a combination of polyelectrolyte and slaked lime. However, when experiments were conducted at high temperatures (20.3 ± 0.1°C), C. perfringens spore log reductions of infinity or 100% were observed with the polyelectrolyte. At increased turbidity, C. perfringens spores log reductions of up to 2.0 or 99.1 ± 0.1% were observed with the polyelectrolyte. The lowest turbidity reduction of up to 24.1 ± 0.8% was observed when slaked lime and activated sodium silicate were used at 20.3 ± 0.1°C. The highest turbidity reduction of up to 99.0 ± 0.1% was observed using a combination of polyelectrolyte and slaked lime for high-turbidity water. This study showed that water purification steps could remove up to 100% of C. perfringens spores when a polyelectrolyte or a combination of polyelectrolyte and slaked lime are used under varying conditions. Therefore, this study recommends using a polyelectrolyte or a combination of a polyelectrolyte and slaked lime for water treatment under specified conditions. A polyelectrolyte and slaked lime combination is recommended for high-turbidity water.
M. Tech. (Department of Biotechnology, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Water purification process; Quantitative Microbial Risk Assessment (QMRA); Clostridium perfringens spores; Protozoan parasites; Polyelectrolyte; Slaked lime; High-turbidity water; Dissertations, Academic -- South Africa.; Water -- Purification -- Biological treatment.